THE CONSTRUCTION AND VALIDATION OF INSTRUCTIONAL DESIGN MODEL FOR ENGLISH AS FOREIGN LANGUAGE INSTRUCTION - Ervina, Ervina; Saharudin, Saharudin; Rusdi, Muhammad (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2014)
The objectives of this research are to propose a specifically designed Instructional Design (ID) model for English as foreign language instruction. The method adopted in developing the proposed ID model is by studying the existing models that have been proposed by many experts and identifying the components of these models. Various theories and perspectives are considered in designing the proposed ID model and integrating the components into the model and their sequences. An ID model for English as foreign language instruction developed in this research consists of seven components which are arranged in mix sequence approach. The components that are connected to the instructional design model are learners needs analysis, learning objectives, instructional materials and sequence, instructional media, instructional strategis, authentic assessment, and performance improvement. The components of the model are arranged following a mix model approach, and thus the model application and use are more flexible. The ID model was validated by two experts through expert reviews and four teachers’ perception. These two experts have indicated that the model has fulfilled internal validation in terms of the components and sequence. Teachers’ perception has given an indication that the model on conceptual basis could be implemented successfully for English as foreign language instruction. Keyword: Instructional Design (ID) model, English as Foreign Language (EFL) instruction